The Cambridge companion to the waste land - McIntire, Gabrielle, Ed (Cambridge companions to literature., 2015)
"T. S. Eliot's The Waste Land is often considered to be the most important poem written in English in the twentieth century. The poem dramatically shattered old patterns of form and style, proposed a new paradigm for poetry and poetic thought, demanded recognition from all literary quarters, and changed the ways in which it was possible to approach, read, or write poetry. The Waste Land helped to define the literary and artistic period known as modernism. This Companion is the first to be dedicated to the work as a whole, offering fifteen new essays by international scholars and covering an extensive range of topics. Written in a style that is at once sophisticated and accessible, these fresh critical perspectives will serve as an invaluable guide for scholars, students, and general readers alike"--